STUDENTS' DIGITAL LITERACY IN ONLINE READING CLASS: A CRITICAL REFLECTION ON ENGLISH LANGUAGE LEARNERS - Rini Estiyowati Ikaningrum; Sri Sarwanti (UIN Raden Mas Said Surakarta, 2021)
Since literacy deals with the ability to read and write therefore information using technologies is really vast developed. In this digital era, students of English need to get accustomed to various disciplines, such as computer, ICT, and media literacy. Digital literacy deals with social practices and conceptions through digital texts. This reveals four main elements, i.e.: understanding cultural, social, and historical contexts of technology use; critical thinking and analysis; reflective practice; and facility with the functional skills and tools of digital technology production. This is a qualitative study which examined students’ critical digital literacy when they did online reading activity outside the class. The data were collected by using questionnaire. The subject of this research were the fourth semester students of English Department of Universitas Tidar Magelang. The findings navigate students with their critical digital literacy and understanding of the text with their background knowledge and interpret text effectively. This research implies to the concept of online class implementation, especially in reading class.